INTENSITAS KEBISINGAN DAN KELUHAN SUBJEKTIF TENAGA KERJA BAGIAN PENGOLAHAN KELAPA SAWIT PADA PT. AGRO MUKO DIKABUPATEN MUKOMUKO PROVINSI BENGKULU - Gustina Indriati; Ertha Meita Pardede (Ensiklopedia of Journal, 2021)
In the processing of oil palm at PT Agro Muko, there are machines whose noise level is 92 dB and the machine is in one building with workers and there is no barrier between the machine and the worker. The purpose of the study was to figure out the description of noise intensity and subjective complaints of the labor of the oil palm processing department. This type of research is descriptive, conducted in PT. Agro Muko, Mukomuko, Bengkulu and conducted in Oktober  – Desember 2020. The population is 73 and all are sampled. Primary data collection by distributing questionnaires by way of questionnaires, secondary data with archives and interview guides by means of interviews and data analysis by means of univariate analysis. The results obtained noise intensity from 4 points of noise measurement obtained 25% ineligible, namely at the engine room point of 92 dB, and 75% qualified at the point of boiler 3, boiler 2, and boiler 1, more than half of respondents with moderate physiological complaints of 64 people (87.7%), more than half of respondents with moderate psychological complaints of 44 people (60.3%) , more than half of respondents with moderate communication complaints were 54 people (74.0%) and more than half of respondents with moderate hearing complaints were 58 people (79.5%) at PT. Agro Muko. HSE's advice is to isolate the source of noise by creating a boundary between workers and generators, setting working hours at a point where the result of measuring noise intensity is 92 dB in accordance with permenaker number 5 of 2018 on occupational safety and health of the work environment and more scheduled and improved supervision of the use of PPE (plug era) at work, so that PAK caused by noise can be prevented.